Preparation of novel polyvinylidene fluoride (PVDF) hollow fiber membranes via thermally induced phase separation - Li, Jieling (2015)
Poly(vinylidene fluoride) (PVDF) has been attached great importance as a membrane material in recent years. With outstanding properties of high mechanical strength, thermal stability, chemical resistance and hydrophobicity, PVDF and copolymers have been widely employed to fabricate hollow fiber membranes, especially with the development of thermally induced phase separation (TIPS) method. Therefore, a better understanding of the factors associated with TIPS process is required to produce high flux PVDF membranes with strong mechanical properties. PVDF hollow fiber membranes were prepared from a series of dope compositions under determined spinning conditions via TIPS technique. Several variables including initial polymer concentration, involvement of PTFE as additive, quenching temperature were studied respectively in each batch of experiment. The fabricated membranes were characterized using different analytical methods comprising scanning electron microscope observation, porosity measurement, mechanical strength test and pure water permeability (PWP) test, etc. The newly developed PVDF hollow fiber membrane can achieve a PWP of 537 LMH with a reinforced mechanical strength (tensile modulus) of 102.2 MPa and a mean pore size below 0.1 μm. Spherulic structures were observed in all membranes suggesting that the solid-liquid separation was the dominant process. It was found that under the PVDF/DMP system, mechanical strength of the membranes obviously increased with the increase of molecular weight of the PVDF polymer or its concentration in the dope solution, which was reflected under SEM observation with denser outer and inner surfaces. When adding PTFE into the dope solution, the water permeability could be drastically enhanced in the PVDF/DMP system. The cooling rate controlled by the air gap and quenching temperature also played an important role in determining the micro-structure and consequently the performance of resultant membranes. The results presenting in this project would be valuable references in the fabrication of PVDF hollow fiber membrane via TIPS for optimized membrane properties.